Various Models of Curriculum Development - Raudhah, Raudhah; Aisyah, Siti; Sanjaya, Bagus; Daud, Muhammad; Panggabean, Hadi Saputra (Universitas Syiah Kuala, 2025)
Curriculum is a fundamental element in education that continuously evolves to adapt to the changing times. This paper aims to review various curriculum development models proposed by educational experts and to analyze the factors influencing curriculum changes in Indonesia. The study employs a qualitative-descriptive approach using a literature review method. The findings reveal that curriculum development models such as those by Tyler, Taba, Wheeler, Goodlad, and the Backward Design each have their own strengths and limitations. Political influences, technological advancements, and social dynamics are identified as the main drivers of curriculum change in Indonesia. The Merdeka Curriculum is considered effective in enhancing character education through project-based approaches and flexible learning structures.